Venous thromboembolism prevention and treatment: expanding the rivaroxaban knowledge base with real-life data. (10th July 2015) - Beyer-Westendorf, Jan; Cohen, Alexander T.; Monreal, Manuel
Abstract: Venous thromboembolism (VTE), encompassing deep vein thrombosis (DVT), and pulmonary embolism (PE) is a potentially life-threatening disease. Patients who acquire VTE are likely to experience recurrent events or life-long morbidities such as post-thrombotic syndrome or chronic thromboembolic pulmonary hypertension. The symptoms associated with VTE are highly variable, ranging from asymptomatic—making diagnosis challenging—to cardiogenic shock. The benefits of anticoagulant for the prevention and treatment of VTE are well established. The clinical development of non-vitamin K antagonist (VKA) oral anticoagulants (NOACs) that specifically inhibit either thrombin or factor Xa has revolutionized the management of VTE, owing to their favourable properties that overcome the limitations of VKAs. These agents have shown favourable outcomes in Phase III randomized controlled trials (RCTs) and are licensed for use in Europe for the prevention of VTE, and the treatment and secondary prevention of DVT and PE. Randomized controlled trials do not reflect routine clinical practice, however, and while NOACs are becoming integrated into treatment protocols, uncertainties remain as to how their benefits apply to patients seen in everyday care. This article will consider these uncertainties, along with data on rivaroxaban use from a number of key non-interventional studies and registries, namely XAMOS, ORTHO-TEP, the Dresden NOAC registry, RIETE, and PREFER in VTE. These data suggest that outcomes with NOACs such as rivaroxaban in RCTs are reproducible in real-life, making these agents a simple, effective treatment choice for a wide range of patients at risk of, or suffering from, VTE.